Slow channel congenital myasthenic syndrome responsive to a combination of fluoxetine and salbutamol. - Finlayson, S; Spillane, J; Kullmann, D; Howard, R; Webster, R; Palace, J; Beeson, D (2013)
INTRODUCTION: Slow channel congenital myasthenic syndrome is a dominant disorder characterized by prolonged acetylcholine receptor ion-channel activation. METHODS: Molecular genetic techniques, electrophysiology, and binding studies in human embryonic kidney (HEK) 293 cells determined mutant function and expression levels. Patient response to treatment was measured by quantitative myasthenic gravis and Medical Research Council grade strength scores. RESULTS: We report an unusual case due to heteroallelic mutations in CHRNE. The slow channel mutation, p.εS278del, is accompanied by a severe low-expression mutation, p.εR217L, on the second allele. Expression studies and cosegregation of p.εS278del with the disorder in the patient's offspring demonstrate robust expression of the p.εS278del mutation. The patient showed modest benefits from standard treatment with fluoxetine, but there was dramatic improvement when salbutamol was combined with fluoxetine. CONCLUSIONS: This case suggests that salbutamol, which is beneficial in some other congenital myasthenic syndromes, might also be considered in addition to fluoxetine in slow channel syndrome.